Brecciation among 2280 ordinary chondrites – Constraints on the evolution of their parent bodies. (1st October 2018) - Bischoff, Addi; Schleiting, Maximilian; Wieler, Rainer; Patzek, Markus
Abstract: After accretion of meteorite parent bodies, larger and smaller collisions have led to significant modifications of these bodies. Involved processes include excavation of material, thermal metamorphism, melting, mixing of different materials, re-accretion, and re-lithification. All these processes can be repeated several times. In this study polished thin sections (PTS) of 2280 chondrites (1193 H, 947 L, and 140 LL chondrites) were investigated in order to obtain the abundance of brecciated rocks among the ordinary chondrites. In addition, we have determined the abundance and characteristics of shock vein-bearing H, L, and LL chondrites and of impact melt rock clasts. We also recognized xenolithic components based on O-isotope studies. Noble gas data were considered in order to detect regolith breccias and to discuss late impact histories. The investigation of 2280 samples shows that 23% (276 of 1193) of the H chondrites, 23% (220 of 947) of the L chondrites, and 79 % (110 of 140) of the LL chondrites are brecciated. Considering the heavily-brecciated LL chondrites in 63 of the 140 chondrites (45%) shock veins were clearly detected. 57 of these 63 chondrites are brecciated rocks. The investigation of the H and L chondrites has shown that about 26% (310 of 1193) of the H chondrites and 40% (379 of 947) of the L chondrites contain shock veins. In our data-set 20% of the H chondrites and 8.3% of the LL chondrites, but only 3.0% of the L chondrites contain solar noble gases. Remarkably, about 62% of all brecciated H chondrites (with noble gases analyzed) contain solar noble gases compared to only around 11% and 10% of the brecciated L and LL chondrites, respectively. The identification of xenolithic clasts (e.g., CI-, CM-, and ureilite-like lithologies) in primitive type 3 chondrites indicates simultaneous accretion of clasts and chondrules. These clasts must have been formed early within the first 2 Ma on subsequently-destroyed precursor, first generation parent bodies. The formation of complex breccias witnesses the collisions between asteroids of very different lithologies and heritage. Although the onion-shell configuration of primordial parent bodies is necessary in order to form the chondrites with different degrees of metamorphic overprint (petrologic types 3–6) subsequent catastrophic fragmentation and reassembly to form asteroids with a rubble-pile structure are required to explain certain features discussed in this work. However, distinct peaks in the cosmic ray exposure age distributions indicate that not too many impacts in the last 100 Ma were responsible to deliver the majority of the ordinary chondritic meteoroids to Earth. Yet, this certainly does not tell anything about the number of "last-generation" parent bodies that exist in the asteroid belt, since S-type asteroids are the most abundant type of asteroid in the inner main belt and thought to be the parent bodies of ordinary chondrites.